Pelatihan dan Pendampingan Analisis dan Pengambilan Keputusan Atas Informasi Laporan Keuangan Berbasis Jaringan Client-Server - Yusnaini; Arista Hakiki; Taufik (Jurusan Akuntansi Fakultas Ekonomu Universitas Sriwijaya, 2025)
This training and mentoring program aims to enhance the competencies of financial and accounting managers at the Employee Cooperative of PT. Pusri Palembang in conducting financial analysis and making data-driven decisions using a client–server–based accounting information system. The benefits of this activity include improving participants’ understanding of financial analysis techniques, increasing efficiency in the reporting process, and strengthening the accuracy, transparency, and accountability of the cooperative’s financial management. The target participants of the program consist of cooperative board members and accounting staff, who serve as key actors in managing and interpreting financial data. The outputs generated from this program include practical skills in reading, analyzing, and making strategic decisions based on financial statements, as well as the publication of a scientific article in a national community service journal. The results of the implementation show a significant improvement in participants’ abilities, both in interpreting financial statements and in applying ratio and trend analysis. This activity contributes to strengthening the institutional capacity of the cooperative to achieve sustainable, data-driven business growth.